The Training and Making of IPS Tools for PGSD FIP Undiksha Alumni in Buleleng Sub-District, Buleleng District - Yudiana, Kadek; Parmiti, Desak Putu; Kusmariyatni, Nyoman; Murda, I Nyoman; Widiana, I Wayan (Universitas Pendidikan Ganesha, 2019)
The process of learning should be good and right, of course, must be supported by various facilities in addition to the ability of teachers to organize learning. The selection and utilization of teaching aids is one of the important things that must be considered by the teacher so that the learning process can be more meaningful and can achieve the expected goals. In reality some elementary school teachers teaching social studies in the Buleleng sub-district rarely use the aid of teaching aids in their teaching and learning process. This happened because some of the teachers considered that to make an IPS teaching aid was very difficult to do, to use these teaching aids in social studies learning took a relatively long time so the teacher decided to teach without teaching aids. Another reason given is that the cost of making IPS teaching aids costs a lot. Based on this, it is deemed necessary to make training for teachers in making simple IPS teaching aids and use them in learning in elementary schools. The activity was attended by 30 people from the Undiksha FIP PGSD alumni teachers. After the implementation of this activity the teacher is no longer having difficulty making IPS teaching aids and is able to use IPS teaching aids well.